Educational activities of schools for children undergoing hospital treatment - Ranković, Dragica L (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2019)
Due to illness and hospitalization some children are more absent from school and, therefore, they miss proper education. The duty of the school is to help students acquire knowledge, skills and habits in accordance with an official curriculum. Hospital treatment allows children to stay in touch with regular educational and social activities. The aim of this paper is to review and compare the educational approaches dealing with the educational work with children on hospital treatment in Serbia and the countries in the region. It is particularly difficult to work with ill children in the hospitals, it requires a huge responsibility, humanity and that is why the lessons have to be adjusted to children’s conditions. The task of hospital schools is to make curriculums more substantial and creative. The sole existence of the schools in hospitals has a therapeutic function regardless of the hospitalization period.  Teachers have to have responsibility towards their work at each moment, due to specific working conditions; they have to strive to make lessons joyful and relaxing so that the children can forget about their illness at least for a moment. In the process, a special attention needs to be paid to schools with so called special categories of students, such as hospital schools.
Keywords: teaching; hospital; hospitalization; special schools; education